1991
DOI: 10.1901/jaba.1991.24-31
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Driving Practices of Pizza Deliverers: Response Generalization and Moderating Effects of Driving History

Abstract: A practical intervention program, targeting the safety belt use of pizza deliverers at two stores, increased significantly the use of both safety belts (143% above baseline) and turn signals (25% above baseline). Control subjects (i.e., pizza deliverers at a third no-intervention store and patrons driving to the pizza stores) showed no changes in belt or turn signal use over the course of 7-month study. The intervention program was staggered across two pizza stores and consisted of a group meeting wherein empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 14 publications
(22 reference statements)
4
39
0
1
Order By: Relevance
“…In addition, this deliverer was observed to decrease his complete stopping notably. This is similar to one pizza deliverer reported in Ludwig and Geller (1991) who decreased his safety-belt use from around 100% during baseline to 0% at one point during the intervention phase.…”
Section: Individual Responsivenesssupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, this deliverer was observed to decrease his complete stopping notably. This is similar to one pizza deliverer reported in Ludwig and Geller (1991) who decreased his safety-belt use from around 100% during baseline to 0% at one point during the intervention phase.…”
Section: Individual Responsivenesssupporting
confidence: 86%
“…Much of our research has found that an increase in a nontargeted behavior can result from an intervention on a similar response class depending on the intervention method (reviewed in Ludwig & Geller, 2000; see also Stokes & Baer, 1977). For example, Ludwig and Geller (1991) intervened to improve safety belt use and observed an increase in drivers' turn-signal use; Ludwig and Geller (1997) also found generalization across nontargeted driving behaviors after an intervention targeting complete stopping. Similarly, Camden, Price, and Ludwig (2009) reported on an absenteeism intervention that also decreased incidents of leaving work early.…”
Section: Abstract Group Versus Individual Feedback Behavior-based Samentioning
confidence: 98%
See 1 more Smart Citation
“…The delivery of feedback to increase safety-related work behaviors has received great attention in the organizational behavior management literature (Fellner & Sulzer-Azaroff, 1984;Ludwig & Geller, 1991, 1997Reber & Wallin, 1984;Williams & Geller, 2000). However, the motivational effects of feedback have been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, behavioral researchers have studied various strategies to increase safety belt use among vehide occupants at work sites (e.g., Geller, 1983;Hagenzieker, 1991;Ludwig & Geller, 1991), schools (Roberts, Fanurik, & Wilson, 1988;Williams, Thyer, Bailey, & Harrison, 1989), and throughout the community (e.g., Geller & Lehman, 1991;Seekins et al, 1988). Most ofthese interventions, however, demonstrated their effectiveness in a single setting or community and were designed to intervene directly with vehide occupants.…”
mentioning
confidence: 99%